PENERAPAN PLATFORM MEDIA SOSIAL PADA USAHA MIKRO MASYARAKAT DESA MENUJU EKONOMI YANG LEBIH BAIK DI KELURAHAN GALANG BARU KECAMATAN GALANG - Rahmat, Muhammad; Efendi, Fadilanata; Cahyani, Aulia Ita; Anwar, Zulvian; Octavia, Tia Kirana; Hutama, Timothy; Meylani, Frina (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
This Field Work Lecture Report discusses the utilization of social media as a strategy to empower micro-enterprises in Galang Baru Village, Galang District, Batam City. The main issue addressed is the low adoption of digital technology by micro-entrepreneurs in the area, particularly in using social media to expand markets and increase sales. The objective of this KKL activity is to enhance the understanding and skills of the community, especially the youth, in using social media platforms such as Instagram, Facebook, and WhatsApp as marketing tools for micro-business products. The methods applied include identifying micro-entrepreneurs, socializing the importance of digitalization, conducting social media training, and providing direct assistance in account creation and content management. Coordination with the village organizational structure was also carried out to support the smooth implementation of the program. The results show an increase in digital awareness and capabilities among micro-entrepreneurs in utilizing social media, despite challenges such as limited internet access and digital literacy. Social media use has proven effective in helping entrepreneurs broaden market reach, build product branding, and significantly increase income. This activity is expected to serve as a sustainable digital-based economic empowerment model for other villages facing similar challenges, while supporting inclusive and responsive local economic development in line with current technological advancements